Depth of Interaction Calibration and Capabilities in 2×2 Discrete Crystal Arrays and Digital Silicon Photomultipliers - Lehnert, Adrienne L (IEEE transactions on nuclear science, 2016)
Digital silicon photomultiplers (dSiPMs) have potential in the advancement of PET detectors. Their advantages include decreased dark counts through selective microcell activation, fast timing, and flexibility configuring event triggering and collection. Further improvements in PET image resolution are possible when photon depth of interaction (DOI) is available, as this reduces parallax error caused by mispositioning events at the peripheral field of view. These improvements are desirable in smaller ring diameter PET systems, such as whole body PET/MRI. In this study we quantify the DOI capabilities of a unique crystal array design (termed dual light sharing arrays or DLSA) that takes advantage of the 2-by-2-pixel die readout logic of a PDPC dSiPM (Philips Digital Photon Counting 3200) device by Philips Medical Systems. The DLSA is comprised of a 2×2 array of 4×4×22 mm3 LYSO crystals; inter-crystal surfaces were optically coupled in part with high-index optical adhesive and optically isolated in complimentary parts with mirror-film reflector such that light sharing was depth-dependent and different along two axes. The DLSA was mounted to one die of a PDPC and its depth-dependent response to 511-keV gamma rays was calibrated using a coincidence-collimated beam from both side and entrance surfaces. Entrance surface DOI calibration was performed through an iterative application of maximum likelihood calculations based on the signal ratio in crystals adjacent to the crystal of interaction. Results showed timing resolutions of 350-370 ps and energy resolutions of 10-12% while achieving a DOI position estimation of 6-7 mm FWHM. Significant improvements in depth estimation error were found when using maximum likelihood estimation and 3-4 depth bins. Furthermore, similar calibration results were obtained for both side-surface and entrance-surface illumination methods, which suggest that PET system calibrations may be easily performed using a monoenergetic flood source with entrance surface illumination